"Demystifying" the police: a participant observation study of police stops (and searches). Issue 1 (2nd January 2016) - Constantinou, Angelo G.
Abstract : Police are empowered by law to stop and search vehicles and their occupants, once reasonable grounds for suspicion come into being. However, as attested by this study, not all suspicions are followed up, nor all stops-searches follow on suspicions. Police stops-searches involve bounteous discretion of whom, where, and when to stop-search, and this process entails a long chain of judgments and actions on behalf of the constables faced with given street-level situations. A six-month complete participant observation study of the Emergency Response Unit of the Cyprus Police resulted in asserting that police stops-searches of vehicles and their occupants rest upon multiple, perplexed, and intertwined factors that range from racial predilections to heat tolerance levels of constables who may or may not be inclined to enforce the law. In all, over one hundred dimensions were found to relate to constables' decision-making process on whether to conduct a stop-search or not.